2020
DOI: 10.1182/blood.2019004596
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind trial of 3 aspirin regimens to optimize antiplatelet therapy in essential thrombocythemia

Abstract: Abstract Essential thrombocythemia (ET) is characterized by abnormal megakaryopoiesis and enhanced thrombotic risk. Once-daily low-dose aspirin is the recommended antithrombotic regimen, but accelerated platelet generation may reduce the duration of platelet cyclooxygenase-1 (COX-1) inhibition. We performed a multicenter double-blind trial to investigate the efficacy of 3 aspirin regimens in optimizing platelet COX-1 inhibition while preserving COX-2–dependent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 45 publications
4
100
0
1
Order By: Relevance
“…60 The possible absence of impact of aspirin on thrombosis and bleeding risk may be due to an insufficient control of platelet COX-1 activity with a once-daily low dose of aspirin. 67 Studies on VKAs or DOACs are also lacking in this population. Such studies have been conducted in the general population, e.g., VKAs versus placebo, 50 DOACs versus VKAs, 51,52 and the combination of DOAC and aspirin versus DOAC and placebo.…”
Section: Discussionmentioning
confidence: 99%
“…60 The possible absence of impact of aspirin on thrombosis and bleeding risk may be due to an insufficient control of platelet COX-1 activity with a once-daily low dose of aspirin. 67 Studies on VKAs or DOACs are also lacking in this population. Such studies have been conducted in the general population, e.g., VKAs versus placebo, 50 DOACs versus VKAs, 51,52 and the combination of DOAC and aspirin versus DOAC and placebo.…”
Section: Discussionmentioning
confidence: 99%
“…78 Finally, we believe it is reasonable to use twice-daily aspirin in patients with arterial thrombosis if they are older or harbor JAK2 mutations or in the presence of CV risk factors (Figures 5 and 6). 47 In patients with venous thrombosis, systemic anticoagulation is advised and the addition of once-daily low dose aspirin, in the presence of JAK2 mutation or CV risk factors, is reasonable. The therapeutic role of direct oral anticoagulants is currently being investigated and has been suggested in retrospective studies, 107 as well as in those with splanchnic vein thrombosis, where recurrence might 108 or might not 109 mutation and without history of thrombosis) and treatment approach in such cases should be individualized.…”
Section: Hydroxyureamentioning
confidence: 99%
“…For patients requiring ASA after discontinuation of the standard anticoagulant treatment, it is important to reassess the response to ASA and in case of low responders to consider alternative prophylactic measures. It has been recently demonstrated that twice daily low dose ASA significantly improves the antiplatelet response in patients with Essential Thrombocythemia, recognized as low-responders to once daily low dose ASA [35] .…”
Section: Discussionmentioning
confidence: 99%